Brain-Derived Neurotrophic Factor is Associated with Self-Reported Quality of Sleep in Type 2 Diabetes Patients in Ghana - Agyekum, Jennifer Adjepong; Yeboah, Kwame (Experimental and Clinical Endocrinology & Diabetes, 2024)
Objective Sleep disturbances are common in patients with type 2 diabetes (T2DM), and this exacerbates disease severity and results in poor quality of life. Brain-derived neurotrophic factor (BDNF) has been reported to mediate the association between T2DM and poor sleep health. The burden of self-reported poor sleep quality and duration in T2DM and their association with serum BDNF levels were investigated.Methods In this case-control design, the Pittsburgh Sleep Quality Instrument was used to assess self-reported sleep quality and duration in 100 patients with T2DM and 80 nondiabetic controls. Sociodemographic data and medical history were collected from case notes and/or using a structured questionnaire. Fasting venous blood samples (5 mL) were collected to measure plasma lipid profile and serum BDNF levels.Results patients with T2DM had low levels of BDNF, poor sleep quality (61.9% vs 27.5%, p<0.001), and shorter sleep duration (6.1±2.2 vs 6.9±1.1 h, p=0.003). T2DM status was associated with doubling the odds of poor sleep quality [OR (95%CI)=2.06 (1.07–6.43), p=0.039] and 1.6 times the odds of short sleep duration [1.63 (1.03–3.79), p=0.028]. Multivariable logistic regression analysis revealed no association between serum BDNF levels and sleep status. However, there was a negative biological interaction between T2DM and BDNF levels on poor sleep quality, resulting in 0.28 relative excess risk due to the interaction and a 12% attributable proportion due to the interaction.Conclusion In this study population, patients with T2DM had a high burden of self-reported poor quality of sleep and shorter sleep duration compared to the nondiabetic controls. T2DM interacts negatively with serum BDNF levels to affect sleep quality.
Keywords: type 2 diabetes; sleep quality; sleep duration; brain-derived neurotrophic factor; Ghana